(untitled) (BioLaw Journal - Rivista di BioDiritto, 2024)
The emerging possibility of incorporating neurotechnologies into products and services that are directly accessible on the market offers new avenues of research. To the best of our knowledge, this article is the first attempt to investigate how the rules of the multilateral trading system can help regulators respond to the challenges posed by these new products and services in the global markets. The study discusses whether the rules of the WTO allow governments to block potentially harmful DTC neurodevices from accessing their internal market; suggests that the rules for standardization and technology transfer may play a positive role in this context; proposes a potential role of the WTO institutional framework in the governance of neurotechnologies.